SIFAT-SIFAT KOPAL MANILA DARI PROBOLINGGO, JAWA TIMUR - Totok Waluyo; E S Sumadiwangsa; Pudji Hastuti; Evi Kusmiyati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Manila copal is originated from the exudate of Agathis sp. trees, which flows out through the tapping stimulation. Manila copal from Indonesia nowadays prevails nearly 80-percent share in the world market. One of the potential regions that produce manila copal in Indonesia is situated in Probolinggo, East Java.The manila copal as such reveals particular physical and chemical properties and then is categorized as superior (U1) and primary (P) qualities, exemplified consecutively: color magnitudes at JO YR 813 (light gray) and 2.5 YR 611 (reddish gray), impurities 9.7 percent and 23.3 percent, softening point 144°C and 149°C, ash content 0.2 percent and 9.2 percent, acid number 244 and 209, saponification number 309 and 245, and specific gravity 0.91 and 0.88, respectively.The qualities of Manila copal from Probolinggo is poor in qualities and could not meet Indonesian National Standard, particularly due to high impurities.